Role of alpha-synuclein protein levels in mitochondrial morphology and cell survival in cell lines. - Min Zhu; Wenwei Li; Chuanzhen Lu (PLoS ONE, 2012)
α-Synuclein is highly associated with some neurodegeneration and malignancies. Overexpressing wild-type or mutant α-synuclein promotes neuronal death by mitochondrial dysfunction, the underlying mechanisms of which remain poorly defined. It was recently reported that α-synuclein expression could directly lead to mitochondrial fragmentation in vitro and in vivo, which may be due to α-synuclein localization on mitochondria. Here, we applied a double staining method to demonstrate mitochondrial morphogenetic changes in cells overexpressed with α-synuclein. We show that mitochondrial localization of α-synuclein was increased following its overexpression in three distinct cell lines, including HeLa, SH-SY5Y, and PC12 cells, but no alteration in mitochondrial morphology was detected. However, α-synuclein knockdown prevents MPP(+)-induced mitochondrial fragmentation in SH-SY5Y and PC12 cells. These data suggest that α-synuclein protein levels hardly affect mitochondrial morphology in normal cell lines, but may have some influence on that under certain environmental conditions.